2017
DOI: 10.5539/ies.v10n11p135
|View full text |Cite
|
Sign up to set email alerts
|

Technology and Early Science Education: Examining Generalist Primary School Teachers’ Views on Tacit Knowledge Assessment Tools

Abstract: For some time a central issue has occupied early science education discussions -primary student classroom experiences and the resulting attitudes towards science. This has in part been linked to generalist teachers' own knowledge of science topics and pedagogical confidence. Recent research in cognitive development has examined the role of so-called tacit knowledge and its potential benefits for supporting conceptual development in children. However, the incorporation of such tools would depend on teachers' wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…Because children will not have come across irregulars too frequently in their early language use, the -ed rule cannot yet be successfully blocked where it would need to be. This explanation, too, chime well with arguments put forward by other studies in science concept development, such as where certain rules -"heavy objects fall faster because they are heavier"are consistently applied in explicitly stated predictions of dynamic events, but simpler recognition tasks can block this rule from being expressed (Hast & Howe, 2015, 2017. And just as increasing exposure to irregulars will eventually help to avoid the overapplication of -ed (Pinker, 1995), relevant intervention tasks have shown that with practice explicit scientific rules can be reformulated in appropriate ways (see e.g., Howe et al, 2013).…”
Section: Overregularisationsupporting
confidence: 67%
See 2 more Smart Citations
“…Because children will not have come across irregulars too frequently in their early language use, the -ed rule cannot yet be successfully blocked where it would need to be. This explanation, too, chime well with arguments put forward by other studies in science concept development, such as where certain rules -"heavy objects fall faster because they are heavier"are consistently applied in explicitly stated predictions of dynamic events, but simpler recognition tasks can block this rule from being expressed (Hast & Howe, 2015, 2017. And just as increasing exposure to irregulars will eventually help to avoid the overapplication of -ed (Pinker, 1995), relevant intervention tasks have shown that with practice explicit scientific rules can be reformulated in appropriate ways (see e.g., Howe et al, 2013).…”
Section: Overregularisationsupporting
confidence: 67%
“…Instead, the naïve ideas may re-emerge under certain conditions, such as when performing under timed constraints (see e.g., Shtulman & Valcarcel, 2012;Shtulman & Young, 2020), just as overextensions can do. It is thus worth noting that conceptual learning is both linguistic and non-linguistic, with a necessary differentiation between children's verbal and non-verbal performance, with the former seemingly being less prone to overextensions (e.g., Hast & Howe, 2015, 2017.…”
Section: Overextensionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study provides a starting point for instructors to reconsider what is taught when and in what manner -which in turn may have implications for their own confidence in teaching (cf. Hast, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…A key challenge for instructors, especially in the earlier stages of classroom-based teaching, is that children bring a wide range of ideas about everyday world phenomena with them (Allen, 2014;Hast, 2014;Hast & Howe, 2012); ideas that are frequently highly resistant to change through instruction (Duit, Treagust, & Widodo, 2013). Teachers are generally not ignorant of this issue (Gomez-Zwiep, 2008;Hast, 2017). However, in the particular context of rainbows and rainbow formation, while little is known from a research perspective, there is evidence to demonstrate that many primary school teachers in fact tend to overestimate their 2 / 6 students' level of understanding (Malleus, Kikas, & Kruus, 2016).…”
Section: Introductionmentioning
confidence: 99%